2018
DOI: 10.1021/acsomega.8b00242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature Stress on Antioxidant Defenses in Brassica oleracea

Abstract: Brassica oleracea crops are exposed to seasonal changes in temperature because of their biennial life cycle. Extreme temperatures (cold and heat) affect the photosynthetic activity and the yield of cabbage (B. oleracea capitata group) and kale (B. oleracea acephala group). We studied the relationship among antioxidant defenses, photosynthesis, and yield under extreme temperatures in both crops. Under these conditions, the plants increase the antioxidant defenses, responding to an increment in reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 29 publications
8
36
1
Order By: Relevance
“…In photosynthesis, ribulose 1,5-bisphosphate carboxylase/oxidase (rubisco) is a key enzyme involved in the xation of CO2 [38]. Rubisco is involved in various physiological responses such as plant growth, photorespiration, glucose metabolism, heat tolerance, low-temperature stress, and salt stress [39][40][41][42][43]. Many studies have shown that the large rubisco subunit is easily degraded under adverse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In photosynthesis, ribulose 1,5-bisphosphate carboxylase/oxidase (rubisco) is a key enzyme involved in the xation of CO2 [38]. Rubisco is involved in various physiological responses such as plant growth, photorespiration, glucose metabolism, heat tolerance, low-temperature stress, and salt stress [39][40][41][42][43]. Many studies have shown that the large rubisco subunit is easily degraded under adverse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress limits plant growth, leaf development, photosynthesis activity, and yield on Brassica (Rodríguez et al 2015;Soengas et al 2018). Moreover, Rurek et al (2018) found that cauliflower closed stomata during heat stress, resulted in moderate photosynthetic with only minor respiratory damage.…”
Section: Discussionmentioning
confidence: 99%
“…In photosynthesis, ribulose 1,5-bisphosphate carboxylase/oxidase (rubisco) is a key enzyme involved in the xation of CO2 [38]. Rubisco is involved in various physiological responses such as plant growth, photorespiration, glucose metabolism, heat tolerance, low-temperature stress, and salt stress [39][40][41][42][43]. Many studies have shown that the large rubisco subunit is easily degraded under adverse conditions.…”
Section: Response Mechanism Of Lysine Crotonylation and Chrysanthemummentioning
confidence: 99%